False Chinch Bug Nysius raphanus Howard (Insecta: Hemiptera: Lygaeidae) - Babu Panthi; Braden Evans; Justin Renkema (EDIS)
The false chinch bug, Nysius raphanus Howard, is a small, greyish, native North American herbivorous seed bug. It is recognized as the most serious pest among members of the genus Nysius, but reports of heavy infestations and serious crop damage are uncommon. Includes: Introduction - Distribution - Description and Life Cycle - Host Plants - Damage - Management - Selected References https://edis.ifas.ufl.edu/in1212